ADOPSI UNSUR-UNSUR INTERNATIONAL CONVENTION FOR THE SUPPRESSION OF TERRORIST BOMBING KE DALAM UNDANG-UNDANG NOMOR 15 TAHUN 2003 TENTANG PEMBERANTASAN TERORISME (STUDI TERHADAP KETERLIBATAN JURNALIS IMAM FIRDAUS SEBAGAI INDIVIDU DALAM KASUS BOM SERPONG) - Joko Setiyono, Aprilia Dwinanda Putri, Dadang Siswanto, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
The Adoption of the 1997 International Convention on terrorist bombing carried out by the Government of Indonesia based on the prohibited act, obligations, elements of jurisdiction, and international cooperation. All four are relevant in the implementation of terrorism punishmentcommitted by domestic law. It became a controversy when terrorism involve the mass media whereas their journalistic code of ethics, for not revealing the information received, but contrary against the International Convention and law onTerrorism Act. For that government should immediately formulate the legislation on terrorism with explosives material which is related to the aspects on journalism.